Chlamydospore formation by Paracoccidioides brasiliensis mycelial form - MArcello Franco; Ayako Sano; Keiji Kera; Kazuko Nishimura; Kanji Takeo; Makoto Miyaji (Revista do Instituto de Medicina Tropical de São Paulo, 1989)
To investigate the role of some adverse environmental conditions in chlamy-dospore formation by the mycelial form of P. brasiliensis, we cultured four P. brasiliensis isolates (18, Bt4, 1183, Pb9) at 25°C within solid agar medium either rich or poor in nutrients. Isolates 18 and 1183 were also cultured under anaerobiosis in a nitrogen atmosphere. Isolate 18 produced great number of terminal and intercalary chlamydospore after 7-10 days of culture in a medium poor in nutrients (2% agar with 0.1% dextrose and polypepton). The three other isolates also produced chlamydospores under the same conditions, but in lower numbers. Chlamydospore production by isolate 18 was abolished when the fungus was cultured in two agar media rich in nutrients (brain heart infusion and potato dextrose agar). Anaerobic incubation of isolate 18 under an atmosphere of N2 showed small mycelial outgrowth with numerous chlamydospores. At the electron microscopical level, the chlamydospores showed one or various nuclei and numerous mitochondria, indicating great potential for further development. Accordingly, chlamydospores produced multiple budding after only 24 h incubation at 35°C. The results demonstrate that under adverse environmental conditions P. brasiliensis mycelial form produces chlamydospores within a short period of time.